Ragam Kultivar Kopi di Lampung - EVIZAL, RUSDI; SUGIATNO, SUGIATNO; PRASMATIWI, FEMBRIARTI ERRY (Agrotrop : Journal on Agriculture Science; Vol 5 No 1 (2015))
Variability of Coffee Cultivars in Lampung. Province of Lampung is production region of Robusta coffee in Indonesia. Farmer plant seedling of progeny resulted in high variability of coffee bean production. High yield clones then were used as grafting material to improve coffee production. The research aimed to study variability of coffee cultivars in Lampung and factors affecting its production. Respondent farmers and coffee fields to be surveyed were determined by purposive sampling method from 3 district of West Lampung, Tanggamus, and North Lampung. Three sub-districts were taken from each district to choose a farmers group. The results showed that there were 27 cultivars found in location including 25 cultivars were Robusta coffee and the rest were Arabica and Liberica. In each district, the compositions of dominant cultivars were different. Farmers were able to describe the cultivars based on characteristics of fruits and beans, leaves, shoots, and branches. Some cultivars come from other province of outside Lampung. Dominance indices and richness of cultivars together with elevation level of coffee field had significant negative effects on coffee productivity, while fertilize doses had positive effects.
Keywords: coffee, cultivars, variability, lampung